Overcoming Barriers to Successfully Commercializing Carbon Dioxide Utilization - Kant, Marvin (Frontiers in Energy Research, 2017)
The successful transition to a low-carbon economy relies on innovative solutions in a global effort. Sustainable entrepreneurship is recognised as a key driver in the creation and transformation of ecologically and socially sustainable economic systems. The purpose of this article is to contribute to this topic by understanding commercialisation barriers for highly sustainability-oriented new technology ventures and to derive recommendations to overcome them. A qualitative multi-level approach is applied to identify barriers and drivers within the internal dynamic capabilities of the organisation and its external stakeholders. Afterwards, a barrier model is developed based on semi-structured interviews with new carbon dioxide utilisation ventures and associated industry players in Canada and the USA, and the European Economic Area. Recommendations to facilitate the (re-)design a dedicated support system were derived on four levels: a) actors, b) resources, c) institutional setting, and d) the coordination of the support system.